2020
DOI: 10.1021/acsami.0c16516
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Discovery of Metal–Organic Frameworks for Methane Adsorption with Hierarchical Screening and Deep Learning

Abstract: In recent years, machine learning (ML) methods have made significant progress, and ML models have been adopted in virtually all aspects of chemistry. In this study, based on the crystal graph convolutional neural networks algorithm, an end-to-end deep learning model was developed for predicting the methane adsorption properties of metal–organic frameworks (MOFs). High-throughput grand canonical Monte Carlo calculations were carried out on the computation-ready, experimental MOF database, which contains approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 71 publications
0
35
0
1
Order By: Relevance
“…It is indicated that the screened 390 PPNs with the high‐performance for acid gas capture exhibit the similar structures. CGCNN algorithms can high‐efficiently extracted feature information from periodic crystal systems and converted it into graph inputs of the convolutional neural network, which can be trained to predict various targeted properties of the crystals 47,51 . Figure 8B shows the parity plots of CGCNN predicted vs. GCMC simulated APS.…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the screened 390 PPNs with the high‐performance for acid gas capture exhibit the similar structures. CGCNN algorithms can high‐efficiently extracted feature information from periodic crystal systems and converted it into graph inputs of the convolutional neural network, which can be trained to predict various targeted properties of the crystals 47,51 . Figure 8B shows the parity plots of CGCNN predicted vs. GCMC simulated APS.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple linear regression analysis has been employed to develop equations to describe methane working capacities at 35–5.8 bar considering the database obtained from high-throughput GCMC calculations 61 of the CoRE MOF database (11 000 MOFs). The details of the methane sorption simulation via GCMC simulations are presented in that work.…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the prediction may be further enhanced by implementing in the equation some more geometrical descriptors: 61 void fraction, LCD (largest cavity diameter) and PLD (pore limiting diameter)Working_capacity (35–5.8 bar) = 36.191 + 0.023 × Sa − 3.405 × Pv − 14.153 × Dc + 35.154 × Vf + 0.689 × LCD − 0.695 × PLD R 2 = 0.899; MAE = 9.26 cm 3 g −1 ; MSE = 159.78; RMSE = 12.63 cm 3 g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…of thermodynamic, mechanical, and electronic properties for 2-D materials, [31] the formation energy of compounds, [32] and the methane adsorption properties of metal-organic frameworks, [33] etc.…”
Section: Introductionmentioning
confidence: 99%
“…One particular example is the recent development of the crystal graph convolutional neural network (CGCNN), [ 29 ] an ML tool that encodes the crystal structure as a "graph," has enabled the accelerated design of crystalline materials with desired properties, while also providing fundamental insights on the elementary/structural contributions to the energetics and properties of the materials. It has been successfully applied to the design of various crystalline materials for specific properties and applications, including the screening of solid electrolytes for dendrite suppression in lithium battery, [ 30 ] prediction of thermodynamic, mechanical, and electronic properties for 2‐D materials, [ 31 ] the formation energy of compounds, [ 32 ] and the methane adsorption properties of metal‐organic frameworks, [ 33 ] etc.…”
Section: Introductionmentioning
confidence: 99%